Perspective Taking and Empathic Emotions in Letters Written by Grandchildren to Their Grandparent With Dementia Versus Grandparent Without Dementia. (February 2020) - Ebert, Alexandria R.; Miron, Anca M.; Hodel, Amy E.; Rowley, Sarah K.; Davis, Rachel; Melotik, Emma
We examined differences in perspective taking and empathic emotions in letters written by young adults with grandparents with dementia (GD; N = 21) versus those with grandparents without dementia (GND; N = 45). College students wrote a letter to either their grandparent with dementia or their grandparent without dementia. The letters were coded for perspective taking and empathic emotions. Perspective taking was operationalized as participants' scores on a perspective-taking orientation scale as well as number of second-person pronouns and number of shared experiences in the letters. Compared with participants in the GND group, those in the GDs group reported greater perspective taking, higher levels of tenderness and empathic distress, but similar levels of sympathy toward their grandparent. These findings suggest that interpersonal interventions should capitalize on family members' higher orientation toward taking the perspective of their family member with dementia and their empathic feelings of tenderness toward that person.